AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA BOS DI SEKOLAH DASAR NEGERI - Munjiah, Siti; M. Daud, Rulfah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to determine the effect of accountability, transparency, and human resource quality on the effectiveness of School Operational Funds (BOS) management in Public Elementary Schools in Banda Aceh. The research is quantitative. The study utilized a proportioned stratified random sampling technique, selecting 84 respondents from 42 elementary schools, including school principals and treasurers. Data was collected through questionnaires and primary data sources and then analyzed using multiple linear regression with SPSS version 26. The research findings indicate that accountability, transparency, and human resource quality simultaneously influence BOS fund management effectiveness. While accountability and transparency were found to affect fund management effectiveness partially, the quality of human resources showed no significant impact on the management process.